Supervisory Competencies of School Heads in Relation to Teachers’ Performance : (JPAIR Institutional Research, 2019)
Supervision is an important indicator of school effectiveness, along with quality teaching, which affects students’ learning. This study aimed to determine the supervisory competencies of school heads concerning teachers’ performance in Secondary Schools in the Titay district. The descriptive-correlational method was used employing a survey questionnaire involving 168 teachers and eight school heads. Data were analyzed using weighted mean, Mann Whitney U-test, Kruskal Wallis H-Test, and Spearman rho correlation coefficient. Findings revealed that school heads were very competent, and teachers were very satisfactory in all indicators except for professional growth and development, and special assignments/tasks. There was no significant difference existed in the supervisory competencies when school heads were grouped according to profile, and no significant difference in the performance when teachers’ were grouped according to age, sex, position, and length of service, however, a significant difference was noted in educational background. Results also revealed a moderate correlation between supervisory competencies and teachers’ performance (Spearman Correlation = ±0.48). Thus, school heads were generally competent, and teachers’ were performing their duties and responsibilities very satisfactorily. However, they need guidance in professional growth and development aspects. The supervisory competencies play an important role since it can be equated with the teachers’ performance; hence, be emphasized in aiming for quality teachers’ performance.